Comparative Analysis of Profitability Drivers of Pig Production Systems in Northern Uganda - Caleb Ibukunoluwa Adewale; Elias Munezero; Elly Kurobuza Ndyomugyenyi; Basil Mugonola (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Pork consumption has risen significantly in many emerging nations, with producers using various systems to meet demand. However, the profitability of these systems remains largely unexplored. Therefore, the drivers of profitability of pig production systems in Northern Uganda were examined. Data were collected using a pretested structured questionnaire through a cross-sectional survey of 240 randomly selected pig farmers. Data were analyzed using descriptive statistics, gross margin analysis, and ordinary least squares model. Results revealed that the cost of initial stock (p < 0.1), cost of feed (p < 0.05), cost of vaccines (p < 0.01), output (p < 0.05), and quantity of feed (p < 0.05) were drivers of profitability in the farrow-to-finish pig production system. Further, profitability in the farrow-to-weaner pig production system was influenced by access to credit (p < 0.1), household size (p < 0.1), access to extension service (p < 0.01), and cost of initial stock (p < 0.05). In the weaner-to-slaughter pig production system, drivers of profitability included access to extension service (p < 0.1), cost of feed (p < 0.1), cost of vaccines (p < 0.05), and cost of initial stock (p < 0.05). Researchers recommend that the government arrange sufficient capacity-building initiatives and training, particularly on the farrow-to-weaner pig production system to increase the output and profitability of this production system. Further, the government and non-governmental organizations should make inputs such as vaccines, drugs, and breeding stock available to pig farmers at competitive market prices to enable farmers to make price-responsive decisions.